Hereditary hemorrhagic telangiectasia associated with inherited thrombophilia - Roganović, Branka; Obradović, Slobodan; Micić, Aleksandar; Petrović, Stanko (Vojnosanitetski pregled, 2017)
Introduction. Hereditary hemorrhagic telangiectasia and inherited thrombophilia are genetic disorders with quite opposite clinical manifestation. The main characteristic for hereditary hemorrhagic telangiectasia is recurrent bleeding, while the main characteristic for hereditary thrombophilia is thrombosis. The association between hereditary hemorrhagic telangiectasia and inherited thrombophilia in the same patient is rare. Case report. We presented a 32-year-old female with recurrent gastrointestinal hemorrhage and epistaxes, during a 9-year period. Hereditary hemorrhagic telangiectasia was established according to “Curaçao” criteria. Three of four criteria have been present: spontaneous recurrent epistaxis, multiple telangiectasias (nose) and visceral lesions (gastric angiodysplasias, jejunal telangiectasias, arterio-venous jejunal fistula). Pulmonary thromboembolism was the first manifestation of thrombophilia; the diagnosis was confirmed by genetic testing. Therapy of hemorrhage with tranexamic acid (anti-fibrinolytic agent;  its use increases risk of thrombosis) was unsuccessful. Remission was achieved by thalidomide. The initial therapy for pulmonary thromboembolism included aspirin (that have an increased risk of bleeding), but aspirin had to be discontinued because of massive hematemesis. Unfortunately, a year later, anticoagulant therapy combined with the proton pump inhibitors, were introduced, because of a new thrombosis. One month after, the patient was still on this therapy, without new episodes of bleeding and thromboembolic events. Conclusion. Hereditary hemorrhagic telangiectasia and inherited thrombophilia could be unrecognized for years, partly due to the lower degree of clinical suspicion. Early diagnosis and the appropriate choice of therapy are essential for reducing serious consequences and to improve quality of life.
Keywords: telangiectasia; hereditary hemorrhagic; thrombophilia; comorbidity; diagnosis; treatment outcome